A Computer System to Manage Physical Spaces: An Approach for FaCENA (UNNE) - Martínez, Sebastián; Alfonzo, Pedro; Marino, Sonia I.; Godoy, María Viviana (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2013)
A web information system is introduced in this paper in order to manage and administer physical space at the Fac-ultad de Ciencias Exactas y Naturales y Agrimensura(FaCENA). The paper presents a web information system to succeed in distributing physical space at the Facultad de Ciencias Exactas y Naturales y Agrimensura (FaCENA), (venue: 9 de Julio street), Universidad Nacional del Nordeste (UNNE), Corrientes, Argentina. The methodology applied is based on prototyping and gradually incorporating changes suggested by potential users. A MySQL database was selected so as to manage infor-mation and the activities performed by users. As regards the users of the system, three profiles were established: firstly, the guests who generate online inquiries and export schedules, and secondly, the users who access the data manipulation and who were grouped as janitors and administrators. The web information system is characterized by a simple and intuitive interface, which allows users to understand and access information easily. Early implementations of the information system show it as a useful, reliable and, consistent tool that takes into account the needs and requirements of the different careers, and provide valuable information about the distribution of classrooms to the students and the staff, considering their schedules and the activities required. Apart from that, the implementation of the system brings about benefits that let the institution innovate in dealing with the activities of janitors, professors and students.